Course Attendance Mobile for Monitoring Student’s Activity - Rijois I. E. Saragih; Thandy Simanjuntak (Geviva Publisher, 2022)
The learning and teaching process is an important activity to achieve learning objectives. However, in practice it often happens that the process does not run as it should. One important component in the learning and teaching process is attendance. The discipline of student attendance shows that they have a good interest in their studies and needs to be recorded so that attendance data is stored and presented properly. Manual attendance recording is a problem of effectiveness and efficiency. This research proposes a system for monitoring student attendance using mobile applications. The results of the study show that it is easier and faster for students to take attendance and easier for teachers to recap student attendance and also become the basis for decision making when giving final grades.